2010
DOI: 10.1002/elps.201000249
|View full text |Cite
|
Sign up to set email alerts
|

Comparative enantioseparations of pharmaceuticals in capillary electrochromatography on polysaccharide‐based chiral stationary phases containing selectors with or without chlorinated derivatives

Abstract: The screening conditions of an existing chiral strategy in CEC were tested for their applicability on four chlorine-containing polysaccharide-based stationary phases. The selectors of these phases are cellulose tris(3-chloro-4-methylphenylcarbamate), amylose tris(5-chloro-2-methylphenylcarbamate), cellulose tris(4-chloro-3-methylphenylcarbamate) and cellulose tris(3,5-dichlorophenylcarbamate). The enantioselectivity of these phases was compared with those of the four phases without chlorine (Chiralpak® AD-RH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…The most widely used polysaccharide‐based CSPs are amylose tris (5‐chloro‐2‐methylphenylcarbamate), cellulose tris (3‐chloro‐4‐methylphenylcarbamate), and cellulose tris (4‐chloro‐3‐methylphenylcarbamate). The advantages and high‐resolving capability of those CSPs in CEC columns toward different analytes have been recently demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used polysaccharide‐based CSPs are amylose tris (5‐chloro‐2‐methylphenylcarbamate), cellulose tris (3‐chloro‐4‐methylphenylcarbamate), and cellulose tris (4‐chloro‐3‐methylphenylcarbamate). The advantages and high‐resolving capability of those CSPs in CEC columns toward different analytes have been recently demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…In more recent work on particle-based polysaccharidetype CSP, newer types of CSP which incorporate chlorinated selectors, i.e. cellulose tris (3- , were tested for their enantioselectivity and used to update the existing screening step of the above strategy for non-acidic compounds [26]. Results revealed that using a column sequence Sepapak 34Chiralcel OD-RH4Sepapak 44Chiralpak AD-RH in the screening step enabled separation of 37 out of 45 compounds, with 20 baseline separated.…”
Section: Polysaccharide Selectorsmentioning
confidence: 98%
“…Cellulose tris(3-chloro-4-methylphenylcarbamate), also known as Sepapak-2 s or Lux Cellulose-2, is a novel CSP which combines both electron-donating and electron-withdrawing substituents. This CSP has been employed only in a few works for HPLC [3,[5][6][7][8][9][10] and CEC [11,12] separation of enantiomers of chiral pharmaceutical compounds. Enantiomers of some amino acid derivatives have been separated with this CSP in normal-phase HPLC [3] but its resolving potential for amino acid derivatives under RP HPLC and CEC conditions has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%